2006
DOI: 10.5551/jat.13.16
|View full text |Cite
|
Sign up to set email alerts
|

A Community-based Picture of Type 2 Diabetes Mellitus in Vietnam

Abstract: There has been a significant increase in the prevalence of type 2 diabetes mellitus (T2DM) in Vietnam. We found that Vietnamese with T2DM had a normal body mass index (BMI), but high levels of total body fat and abdominal fat.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 32 publications
0
6
1
Order By: Relevance
“…Most of subjects with the disease had not undergone appropriate treatment and management at the study sites. Meanwhile, the detection rate of diabetes in the present study was markedly lower than previously reported (2001) in Vietnam: 6.9% among adults in Ho Chi Minh City and 5.8% in Hanoi, compared with the present findings of 1.1% with high blood glucose level (≥200 mg/dl; ≥11.1 mmol/l) and 0.8% with elevated HbA1c (≥6.5%) [8, 11]. Our diagnostic criterion for diabetes was higher than 200 mg/dl of blood glucose level because most subjects were examined after a meal, but fasting blood glucose level was not taken into account in this study.…”
Section: Discussioncontrasting
confidence: 55%
See 1 more Smart Citation
“…Most of subjects with the disease had not undergone appropriate treatment and management at the study sites. Meanwhile, the detection rate of diabetes in the present study was markedly lower than previously reported (2001) in Vietnam: 6.9% among adults in Ho Chi Minh City and 5.8% in Hanoi, compared with the present findings of 1.1% with high blood glucose level (≥200 mg/dl; ≥11.1 mmol/l) and 0.8% with elevated HbA1c (≥6.5%) [8, 11]. Our diagnostic criterion for diabetes was higher than 200 mg/dl of blood glucose level because most subjects were examined after a meal, but fasting blood glucose level was not taken into account in this study.…”
Section: Discussioncontrasting
confidence: 55%
“…In Vietnam, their lifestyle is changing quickly along with rapid economic growth. Accordingly, the prevalence of diabetes in adults in Hanoi increased from 1.3% in 1990 to 5.8% by 2001 [7, 8], and the prevalence of CKD is also expected to increase considerably there in the near future.…”
Section: Introductionmentioning
confidence: 99%
“…The extent of this increased prevalence is evident in a recent study conducted by Ta et al, (2010), in Ho Chi Minh city, Vietnam, where rates of T2DM were found to be 10.8% of men and 11.7% of women, compared to approximately 7% in Australian populations [ 1 ]. Additionally, while the average BMI of Caucasians with T2DM is approximately 26–27.5/m 2 , [ 16 ], the average BMI of Vietnamese T2DM patients is around 23 kg/m 2 [ 17 ]. As well as occurring at lower BMI levels, rates of T2DM increase more rapidly in the Vietnamese, with even modest increases in BMI [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…As well as occurring at lower BMI levels, rates of T2DM increase more rapidly in the Vietnamese, with even modest increases in BMI [ 12 ]. This overall increased prevalence of T2DM is thought to be linked to greater levels of abdominal and visceral adiposity in Vietnamese individuals [ 17 , 18 ] compared to other ethnicities.…”
Section: Introductionmentioning
confidence: 99%
“…The meaning of self-care may also possibly be associated with the context of a disease trajectory, healthcare culture, individual attitudes, personalities and cultural beliefs. However, contemporary literature about type 2 diabetes in Vietnam has focused on the prevalence (N. Son, Trung, Kaoru, & Shigeru, 2006), the risk factors (Chan et al, 2009;L. Son, N,T,D., et al, 2004;N.…”
Section: Rose and Harris (2006) Who Conducted Qualitative Interviews ...mentioning
confidence: 99%